Interculturalidad y Reconocimiento Revitalización del conocimiento indígena en la pedagogía intercultural: Enseñanza, práctica y lengua - Zuchel, Lorena; Albertsen, Torben; Salas Astrain, Ricardo (Ariadna Ediciones, 2023)
The revitalization and intercultural teaching of indigenous knowledge presents challenges for the educational and intercultural system; challenges that involve not only curricular content, but also methodologies. From here we see, for example, that the Chilean educational system is formal and largely based on writing, while the knowledge of indigenous peoples places emphasis on informal learning contexts and oral transmission. This book is the result of intercultural dialogues that occurred at the Federico Santa María Technical University, Valparaíso, Chile, while the possibility of having a new Constitution for the country was debated. We present it here with the hope of contributing to the discussions on the reformulation of the educational system in order to undo traditional asymmetries and install interculturality at the very core, paving the way for a society where interethnic and interlinguistic relations are not circumstantial or a mere decoration. cultural.